A theoretical study on the effect of heteroatoms (N, B, Si) on the interaction of aluminum clusters with a carbon graphene-like plane - E. M. Demianenko; M. I. Terets; L. M. Ushakova; S. V. Zhuravskyi; Yu. I. Sementsov; V. V. Lobanov; O. V. Filonenko; V. S. Kuts; A. G. Grebenyuk; M. T. Kartel (Хімія, фізика та технологія поверхні)
It is known that the addition of a small amount of carbon nanomaterials significantly improves the mechanical properties of composites with a metal matrix. One of the most important, promising and available metals as a matrix for such modification is aluminum. However, at the interface between the carbon material and Al, aluminum carbides of different composition are formed, which are brittle and have the main disadvantage - solubility in water. Therefore, the appearance of aluminum carbide is a serious problem, since it contributes to the formation of defects, which, when the composite is deformed, leads to cracking of the composite due to the presence of microneedles. In this regard, in order to predict the features of the interaction of aluminum itself with the surface of carbon nanomaterials, it is advisable to model such processes using quantum chemistry methods.